2013
DOI: 10.1016/j.immuni.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Macrophage-Colony Stimulating Factor Induced Zn Sequestration Enhances Macrophage Superoxide and Limits Intracellular Pathogen Survival

Abstract: SUMMARY Macrophages possess numerous mechanisms to combat microbial invasion, including sequestration of essential nutrients, like Zn. The pleiotropic cytokine granulocyte macrophage-colony stimulating factor (GM-CSF) enhances antimicrobial defenses against intracellular pathogens such as Histoplasma capsulatum, but its mode of action remains elusive. We have found that GM-CSF activated infected macrophages sequestered labile Zn by inducing binding to metallothioneins (MTs) in a STAT3 and STAT5 transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
258
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(266 citation statements)
references
References 42 publications
8
258
0
Order By: Relevance
“…8 Furthermore, zinc deprivation of Histoplasma capsulatum has been shown to lead to increased susceptibility of the pathogen against ROS, whereas at the same time zinc accumulation improves ROS-tolerance of the host cell. 30,31 Oxidative burst is increased by zinc deficiency during macrophage differentiation. 11 Accordingly, in the present study zinc deficiency promotes the oxidative burst of human monocytes, but seemingly only in response to GFP-S. aureus, thereby excluding a general effect.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, zinc deprivation of Histoplasma capsulatum has been shown to lead to increased susceptibility of the pathogen against ROS, whereas at the same time zinc accumulation improves ROS-tolerance of the host cell. 30,31 Oxidative burst is increased by zinc deficiency during macrophage differentiation. 11 Accordingly, in the present study zinc deficiency promotes the oxidative burst of human monocytes, but seemingly only in response to GFP-S. aureus, thereby excluding a general effect.…”
Section: Discussionmentioning
confidence: 99%
“…In the villus of the small intestine, ZnT4 expression is dramatically increased during differentiation (16). Upregulation of ZnT4 mRNA expression, along with ZnT7 mRNA by GM-CSF in macrophages, may contribute to the phagocyte antimicrobial effector function by shuttling zinc away from phagosomes through the mobilization of zinc into the Golgi apparatus (388). ZnT4 expression decreases in the progression from benign to invasive prostate cancer (153).…”
Section: Znt4mentioning
confidence: 99%
“…Metal analysis demonstrated that total Zn content was increased within activated macrophages infected with the fungal pathogen Histoplasma capsulatum (78). This was the result of increased Zn import via the ZIP2 importer, but the Zn ion was then distributed to intracellular Decreased survival [70] organelles such as the Golgi apparatus via Zn transporters ZnT4 and ZnT7 or bound to metallothionein (78). By contrast, LPS binding to the TLR4 receptor does not trigger Zn import into the macrophage.…”
Section: Alterations In Host Cu and Zn Status In Response To Bacteriamentioning
confidence: 99%